Determinants Of The Profitability Of Islamic Commercial Banks In Indonesia - Tusiyani, Ira; Yudiana, Fetria Eka (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2024)
Factors that influence bank profitability can come from various performances. One of the profitability ratios used is Return On Assets (ROA), which is a profitability ratio that shows the percentage of profits to determine the company's efficiency in managing assets to generate profits. Other factors that influence profitability include Third Party Funds and Non-Performing Finance. The aim of this research is to examine the influence of DPK and NPF on profit sharing financing at Islamic commercial banks in Indonesia in 2016-2020. This type of research is quantitative, using data collection techniques with purpose sampling. This research also uses panel data analysis techniques, namely a combination of time series and cross section data. The panel data regression model is a combination of data from a number of objects within a certain time period. The total population is 14 Islamic commercial banks in Indonesia, with a sample size of 10 Islamic commercial banks in accordance with the characteristics of this research. This research uses a panel data regression analysis method which is processed using eviews 10. The results of this research are that DPK has a negative and insignificant effect on profitability. NPF has a positive and insignificant effect on profitability. Profit sharing financing has a positive and significant effect on profitability. DPK has a positive and significant effect on profit sharing financing. NPF has a negative and significant effect on profit sharing financing. Profit sharing financing does not mediate TPF and NPF on profitability.